How do world class top 5 Giro d'Italia finishers train? A qualitative multiple case study - Gallo, G.; Mateo-March, M.; Gotti, D.; Faelli, E.; Ruggeri, P.; Codella, R.; Filipas, L. (Scandinavian Journal of Medicine & Science in Sports, 2022)
The aim of this study was to describe individual training strategies in preparation to Giro d'Italia of three world class road cyclists who achieved a top 5 in the general classification. Day-to-day power meter training and racing data of three road cyclists (age: 26, 27, 25 years; relative maximum oxygen consumption: 81, 82, 80 ml/min/kg; relative 20-min record power output: 6.6, 6.6, 6.4 W/kg) of the 22 weeks (December-May) leading up to the top 5 in Giro d'Italia general classification were retrospectively analyzed. Weekly volume and intensity distribution were considered. Cyclists completed 17, 22, 29 races, trained averagely for 19.7 (7.9), 16.2 (7.0), 14.7 (6.2) hours per week, with a training intensity distribution of 91.3-6.5-2.2, 83.6-10.6-5.8, 86.7-8.9-4.4 in zone 1-zone 2-zone 3 before the Giro d'Italia. Two cyclists spent 55 and 39 days at altitude, one did not attend any altitude camp. Cyclists adopted an overall pyramidal intensity distribution with a relevant increase in high-intensity volume and polarization index in races weeks. Tapering phases seem to be dictated by race schedule instead of literature prescription, with no strength training performed by the three cyclists throughout the entire periodization.